The Umland of Hamilton, Ontario - Peart, Helen (My University, 1953)
Every city possesses and umland, an area adjacent to the city, within which economic, cultural, and social activities are focused on that city. The size of the umland is determined chiefly by two factors, the size of the city, and its location. A large city usually will have a large umland, but if it is situated in an area of urban concentration, the extent of the umland will be limited through competition. Hamilton is a city such as this. Near it is Toronto, a large and influential city which restricts Hamilton's regional development. Closer are the smaller cities of Guelph, Galt, Brantford and St. Catherines, all of which have their own umlands, and all of which compete with Hamilton. The term umland implies an interrelationship between the city and the region. The city performs services for the region, and distributes goods to it. In turn, the region supplies provisions for the urban market, and workers and buyers for its industrial and commercial enterprises. This relationshup may or may not be close. Hamilton is an industrial city, with little dependence on the region. However, the region looks to the city to supply some of its needs. It is the purpose of this thesis to show the relationship between Hamilton and its umland, and to explain some of the factors which determine the extent of that umland.
Keywords: umland; hamilton, ON; ontario; geography